FORAMINIFERAL BIOSTRATIGRAPHY AND PALAEOENVIRONMENTAL INTERPRETATION OF WELL – 004 (OML – 34) CENTRAL - Abubakar, Usman; Hamza, Halidu; Obiosio, Enam Okon; Najime, Tavershima; Usman, Musa Bappah (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
A total of seventy – two ditch cutting samples from well – 004 in OML – 34 onshore Niger Delta were described and analyzed for their foraminiferal content. Lithologic description of the samples shows that the entire sediments belong to the paralic sequence of Agbada Formation. A total of sixty three foraminiferal species were recovered out of which forty – five were benthonics and eighteen are planktonics. The planktonic foraminifera index species recovered from the well revealed that the sediments penetrated in the well range in age from Late Oligocene to Early Middle Miocene. Five planktonic foraminiferal zones namely Globigerina ciperoensis - Globorotalia opima nana Interval zone, Globigerina ciperoensis - Globigerinoides altiaperturus Interval zone, Globigerinoides altiaperturus – Catapsydrax dissimilis Interval zone, Catapsydrax dissimilis - Catapsydrax stainforthi Interval zone and Catapsydrax stainforthi - Praeorbulina sicana Interval zone have been identified based on First Downhole Occurrences and Last Downhole Occurrences of the planktonic foraminiferal index forms. Based on the triangular plot of the wall composition of the foraminiferal suborders the sediments in the study well are considered to be of normal salinity depositional environment deposited in dysoxic to oxic condition. Paleobathymetric ranges of some selected benthic foraminifera species shows that the palaeobathymetry of the studied well section ranges from non-marine to outer neritic.